Estudo sobre os métodos convencionais de reabilitação e reforço de estruturas de aço - Ferreira Filho, José Osvaldo (2017)
Rehabilitation and strengthening of structures are viable and sustainable alternatives for the construction improvement. Repaired and strengthened structures are common and investments in this area occur mainly in Europe countries and in the United States. However, in Brazil, studies and researches about this topic are rarely published in the technical field. In this sense, this work aimed to examine and present conventional methods for the rehabilitation and strengthening of steel structures which involve the cutting and replacement of steel members or addition of steel plates, considering their applications and technical feasibility. For this, it was necessary to understand the fundamentals of structural analysis, the design and pathologies of steel constructions. It was also required to study the relevance of repair and reinforcement and describe the main methods. In this case, publications were bibliographically reviewed mainly the international ones. Therefore, it was concluded that repair and strengthening have economic advantages and there is not a considerable number of conventional methods diffused, standardized, and applied in Brazil. At the end, the work resulted in a report with relevant information available for engineers and architects.